Catch-up growth in preterm neonates with bronchopulmonary dysplasia in the first 2 years of life - Daniela R. Couto; Glória Gonçalves; Gustavo Rocha; Filipa Flor-; Hercília Guimarães (Hygeia Press di Corridori Marinella, 2021)
Bronchopulmonary dysplasia (BPD) is a serious problem in Neonatal Intensive Care Units (NICUs). It is a multifactorial disease that may influence the growth and development of preterm neonates. The aim of this retrospective case-control study of preterm infants with BPD who were born in our centre was to evaluate the growth of these infants in the first 2 years of life compared with healthy preterm infants and to determine risk factors associated with poor growth. Those with major congenital malformations, congenital TORCH infection, deceased before 36 weeks of postmenstrual age or during the first 28 days of life and those who were transferred during hospitalization and outborn neonates were excluded. A total of 90 preterm neonates were enrolled and 30 (33.3%) of them had BPD. At 12 months of corrected age, gestational age and pre-pregnancy mother's weight were shown to be associated with short stature. Weight at birth was also associated with low weight and head circumference growth. At 12 months after term, no differences were found within the growth assessment. Our study showed that growth between 12 and 18 months of life in preterm infants with BPD was sufficient to catch up.